Upcoming therapies for steatotic liver disease: Translating breakthroughs into clinical practice - Philip N. Newsome; Saima Ajaz (Journal of Internal Medicine, 2026)
Abstract Metabolic dysfunction‐associated steatotic liver disease (MASLD) is the most common chronic liver disease worldwide and a leading cause of cirrhosis, hepatocellular carcinoma, and cardiometabolic morbidity. Often clinically silent until advanced fibrosis develops, management has largely relied on lifestyle interventions, with limited pharmacological options and inconsistent risk stratification. Recent advances in noninvasive diagnostics and targeted therapies are beginning to transform this approach. This review examines the evolving management paradigm of MASLD and metabolic dysfunction‐associated steatohepatitis (MASH), focusing on practical implementation of fibrosis‐based risk stratification, structured care pathways, and newly approved or late‐stage pharmacological therapies. Recent clinical trials demonstrate that therapies targeting metabolic dysfunction and hepatic fibrogenesis can improve steatohepatitis and fibrosis, particularly in patients with advanced disease. Incretin‐based therapies have shown MASH resolution in approximately 40%–60% of patients, accompanied by weight loss of 10%–20%, whereas thyroid hormone receptor‐β agonists have demonstrated substantial reductions in liver fat and improvements in fibrosis‐related endpoints. Emerging fibroblast growth factor analogs and combination therapeutic approaches suggest additive benefit through complementary metabolic and anti‐fibrotic mechanisms. Together, these advances support treatment strategies guided by fibrosis risk rather than steatosis alone. MASLD care is therefore moving from reactive disease management toward structured pathways that integrate scalable diagnostics with disease‐modifying therapy, offering the potential to alter disease progression and reduce the burden of advanced liver disease.